Development of solar cells for IoT applications - Lee, Gloria Jie Yi (Nanyang Technological University, 2021)
The Internet of Things (IoT) has been capturing the attention of many with the increase in use of the Internet. Today, IoT applications can be found widely in our daily lives, with projections to further increase in the future. The use of IoT requires the deployment of wireless sensor nodes (WSN) which in turn requires power consumption. Due to ease of deployment and the requirement for the WSN to be less conspicuous, the current trend in the industry is on the miniaturisation of the IoT-WSN and to reduce the reliance on the use of batteries. Employing photovoltaic cells (PV) which harvests light energy allows the energy to be converted and stored in the battery, which can then be used to power the IoT circuit. Improvements are made in order to minimise the size of the circuit and reduce the footprint of the PV solar cells to achieve a maximum output power per unit area. This research focuses on the development of PV solar cell as a source of energy for the IoT circuit. The construction of the IoT circuit board was first done with the various hardware components and subsequently, the software portion, which utilises a cloud server. With the integration of the solar cell into the circuit, the battery can be charged in the presence of light and real-time data could be sent over to the cloud server where measurements would be recorded. Besides conventional planar solar cell, we also study PV-Tower solar cell, which is a three-dimensional solar cell with a high aspect ratio to enhance the light energy absorbed over a small footprint. Comparisons between the conventional planar solar cell and the PV-Tower solar cell were also done to determine their respective performances and efficiencies in the outdoor and indoor environments.